PROBLEMS RELATED TO INTELLECTUAL PROPERTY AND CHILDREN’S EDUCATION: बौद्धिक सम्पदा और बच्चों की शिक्षा से सम्बन्धित समस्याए - singh, Ompal; Singh, Hamendra (International Journal of Research -GRANTHAALAYAH, 2018)
Education is the cornerstone of human life. Only through education can a person be able to achieve a specific personality. Sometimes illiterate person is also effective; However, due to lack of education, he is mainly attached to his environment, due to which he is often unable to give wide range of his specialties so that he can benefit the entire Indian and foreign citizens. The current global scenario indicates that a country whose citizens are deprived of education cannot sustain on the global plane. In the Indian perspective, many problems related to children’s education are becoming visible, due to which every section of Indian society is not developing equally. Even after many government schemes, the problems related to children’s education remain the same and Indian intellectual property is declining. शिक्षा मानव जीवन का श्रंृगार है । शिक्षा के माध्यम से ही व्यक्ति एक विशिष्ट व्यक्तित्व को प्राप्त करने में सक्षम हो सकता है । अनेक बार अशिक्षित व्यक्ति भी प्रभावशील होता है; परन्तु, शिक्षा के अभाव में वह मुख्य रूप से अपने परिवेश से ही अधिकतम जुड़ा हुआ रहता है जिस के कारण वह अपनी उन विशिष्टताओं को व्यापक रूप प्रदान करने में प्रायः अक्षम रहता है जिन से कि वह सम्पूर्ण भारतीय और विदेशी नागरिकों को लाभ पहुँचा सके । वर्तमान वैश्विक परिदृश्य यह संकेत करता है कि वह देश वैश्विक धरातल पर टिका नहीं रह सकता जिस के नागरिक शिक्षा से वंचित हैं । भारतीय परिप्रेक्ष्य में बच्चों की शिक्षा से सम्बन्धित अनेक समस्याएँ दृष्टिगोचर हो रही हैं, जिस के कारण भारतीय समाज का प्रत्येक वर्ग समान रूप से विकसित नहीं हो रहा है । अनेक शासकीय योजनाओं के पश्चात भी बच्चों की शिक्षा से सम्बन्धित समस्याएँ पूर्ववत ही हैं और भारतीय बौद्धिक सम्पदा में कमी हो रही है ।